Effect of Plant Populations on Growth and Yield of Maize (Zea mays L.) in an Intercropping Pattern with Soybean (Glycine max L.) - Alyadin, Faadhilah Fairuz; Sumarni, Titin (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2024)
Maize (Zea mays L.) and soybean (Glycine max L.) are the second and third most important food crops after rice in Indonesia. In order to utilize land resources efficiently and increase production factors optimally, it is necessary to plant with an intercropping system and treat population differences so that there is no competition between intercropped plants. The purpose of this study, among others, to determine the most appropriate population size on the growth and yield of maize plants with an intercropping pattern of maize and soybeans. The research was conducted at April 2021 to July 2021 at the Experimental Garden of Brawijaya University, Jatimulyo, Lowokwaru District, Malang City, East Java. This study was a non-factorial experiment using a Randomized Block Design (RBD) consisting of 6 treatments which were a combination of corn spacing and different populations on soybeans. The results showed that the treatment of plant spacing and different populations in intercropping maize with soybeans was able to increase growth and yield of maize. Maize with wide planting distance was intercropped with low population of soybeans had a larger leaf area growth of 3.71 m2, an increase of 26.41% compared to